Parathyroid carcinoma, a rare cause of primary hyperparathyroidism - Alperstein, Adam (BMJ Publishing Group, 2014)
A 45 year-old woman who presented with non-specific neck and shoulder pain, was found to have mild hypercalcaemia, markedly elevated parathyroid hormone levels, and an irregular parathyroid gland on imaging. The patient underwent a parathyroidectomy and the pathology report came back positive for parathyroid carcinoma with muscular invasion. Parathyroid carcinoma is an exceptionally rare cause of primary hyperparathyroidism and can have a poor prognosis due to metastases and a high propensity to recur after resection. Reports of non-functioning parathyroid carcinomas tend to behave even more aggressively. Repeat imaging on this patient showed residual cancer present, so the patient underwent a second surgery with radical neck dissection and has since been doing very well postoperatively. Diagnosis and treatment is challenging and it is critical to continuously follow-up for recurrent disease.